Bahasa Inggris - Lauha, Fitriyanti; Yusri Halada; La Ode Sultan (LPPM Universitas Bina Mandiri Gorontalo, 2023)
The duration of venous blood damming of 2 minutes greatly affects the results of the examination, because it can cause the results of the examination to increase or decrease and damage the blood specimen. This study aims to determine the number of platelets from the results of the examination of the duration of venous blood sampling using 1 minute and 2 minutes.The method in this study used descriptive quantitative to do two treatments, namely the length of damming the venous blood collection using 1 minute (Normal) and 2 minutes (Abnormal).The results showed that routine blood tests were influenced by pre-analytical, analytical, and post-analytic factors. Among them are pre-analytic factors that affect routine blood, the duration of damming venous blood collection for 2 minutes greatly affects the results of the examination, because it can cause the results of the examination to increase or decrease and damage the blood specimen.